Failure to protect: lessons from Kenya’s IDP network - Prisca Kamungi; Jacqueline M Klopp (Forced Migration Review, 2007)
State-instigated violence in the 1990s in Kenya left thousands dead and hundreds of thousands displaced. Today some 430,000 IDP's live in abysmal conditions. This is in spite of the fact that Kenya has an IDP support network, a vibrant civil society and, since a historic election in 2002, political freedom to organise. What has gone wrong?